Estimation of Serum Thyroid Stimulating Hormone and Anti-Thyroid Antibodies as Biomarkers of Malignancy in Thyroid Nodule Patients - Khaulah Qureshi, Mushayyada Rathore, Noor-Ul-Ain Waheed, Sehrish Lodhi, Nighat Yasmin, Aamir Jamal Gondal, Nakhshab Choudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out association of Serum Thyroid Stimulating Hormone (TSH) and Anti-Thyroid Antibodies (ATA) i.e., anti Tg-Ab & anti TPO-Ab with thyroid carcinoma in thyroid nodule patients presented in Mayo Hospital Lahore. Study design: It was a comparative cross-sectional study. Methods: It wasconducted in Biochemistry Department and Department of Biomedical Sciences KEMU, Lahore from February 2018 to May 2019. Seventy patients were included in the study based on selection criteria and data was recorded on a preformed questionnaire. The study participants were classified into benign (n=36) and malignant categories (n=34) based on histopathological & radiological investigations. Serum levels of TSH and anti- thyroid antibodies (TPO-Ab&Tg-Ab) were measured employing ELISA (Enzyme Linked Immunosorbent Assay) technique. Results: Thyroid nodules were found to be more prevalent in females (n=64, 91.4%). The mean age of the study subjects was 38.46±12.92 years and there was a significant association of older age with thyroid carcinoma (p=0.001). Moreover, Serum TSH, Anti-Tg-Ab and TPO-Ab were higher in malignant than in benign thyroid nodules and were significantly associated with thyroid cancer (p=<0.05). Furthermore, a binary logistic regression analysis concluded that higher serum TSH levels may increase the risk of malignancy in thyroid nodule patients (OR=5.124). Conclusion: Older age and higher levels of serum TSH, Tg-Ab and TPO-Ab showed a significant association with thyroid carcinoma in thyroid nodule patients. Keywords: Thyroid carcinoma, Thyroid stimulating hormone, Anti- thyroglobulin Antibody, Anti-TPO antibodies, Thyroid nodule